Mini-implant-anchored Mesialslider for simultaneous mesialisation and intrusion of upper molars in an anterior open bite case: a three-year follow-up - Wilmes Benedict; Katyal Vandana; Willmann Jan; Stocker Bruce; Drescher Dieter (Sciendo, 2015)
The present case report describes the orthodontic treatment and long-term follow-up of an adult female patient (27 years) who was diagnosed with a mild Class III malocclusion characterised by an anterior and lateral open bite and three periodontally-compromised first permanent molars.